2013
DOI: 10.1177/0363546513503289
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Medial Collateral Ligament Anatomic Augmented Repair Versus Anatomic Reconstruction

Abstract: These results suggest that both an anatomic sMCL augmented repair and an anatomic sMCL reconstruction improve knee kinematics compared with a deficient sMCL and provide equivalent joint stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…3,6 In regard to diagnosis, stress radiographs should be used in all patients with a clinical suspicion of a medial side injury. LaPrade et al 8 reported that the amount of medial compartment gapping can be quantified on valgus stress radiographs for medial knee injuries in the acute and chronic settings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,6 In regard to diagnosis, stress radiographs should be used in all patients with a clinical suspicion of a medial side injury. LaPrade et al 8 reported that the amount of medial compartment gapping can be quantified on valgus stress radiographs for medial knee injuries in the acute and chronic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques have been shown to restore normal laxity of the joint in the most tested conditions. 3,6 Long-term studies should be performed to ensure the maintenance of the restoration, stability, and functionality of the knee. We encourage other groups to test the validity of this technique to assess for long-term results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations